Teacher Improvisation as Processes of Mosaic, Kaleidoscope and Rhizome - an arts-based, co-teaching approach - Hannah Kaihovirta (Cappelen Damm Akademisk NOASP, 2017)
The aim for this article is, based on theory, and through practice, to generate awareness on an activity that many teachers perform; the practice of improvisation. Improvisation is a professional method in teaching practice that very often is so taken-for-granted that it is to some extent under-theorized in the area of educational research. In education, an important purpose of the robustness of research involves educational practice. Therefore, the article is informed by a deductive discourse, where theory leads practice. The practice investigated is based on arts-based co-teaching project experiences made in a primary school in Vaasa, Finland in the school year 2015-2016. One theory that interested me as a form of artist-researcher-teacher intervention in the project was teacher improvisation. In the article improvisation is approached from a position formed by a combination of improvisation mindsets and participatory research practice. My researcher identity and the research method are informed by a/r/tography. This means that the inquiry is interpreted as an evolving process where the article production is part of the process. As a result, I create representations that I suggest to function as three mindsets about improvisation in teaching: the mosaic, the kaleidoscope and the rhizome.